Maximizing forage yield and quality of grasses through nutrient management in established coconut (Cocos nucifera) orchards - SHEKARA, B G; MAHADEVU, P; CHIKKARUGI, N M; SANNAGOUDAR, MANJANAGOUDA S; MANASA, N; RAJANNA, G A; PARAMESH, V; HALLI, HANAMANT M; SHANTHARAJA, C S (The Indian Journal of Agricultural Sciences, 2025)
The aim of crop intensification is to harvest the maximum biomass per unit area and improve the resources use efficiency in face of increasing food demand and decreasing land availability. The experiment was conducted from 2020–2022 at Zonal Agricultural Research Station, Vishveshwaraiah Canal Farm, Mandya, Karnataka to assess the performance of different forage grasses under varied nutrient levels in the established coconut (Cocos nucifera Linn.) orchard. Treatment consisted of three fodder grasses (Bajra Napier hybrid, Guinea and Signal grass) and three nutrient levels [(100% Recommended dose of nutrients (RDN), 125% RDN and 150% RDN). Experiment was laid out in factorial randomized block design (FRBD) and replicated three times. The results revealed that Bajra Napier hybrid grass produced significantly highest forage (832.14 q/ha), dry matter (181.48 q/ha) and crude protein yield (12.55 q/ha). Application of 150% RDN across grasses recorded maximum green forage (694.09 q/ha), dry matter (163.88 q/ha) and crude protein yield (12.73 q/ha). Similarly, bajra napier grass under 150% of RDN harvested the highest forage yield (492.23 q/ha) due to maximum light interception at the bottom (39.19%) and middle (29.18%) of the coconut canopy. Consequently, improved net returns and benefit cost ratio were noticed in this treatment combination. Therefore, productivity and profitability of established coconut orchards could be enhanced through inclusion of high yielding Bajra Napier hybrid grasses with intensive nutrient application. These results can be extrapolated to the coconut growing regions of the country to meet the green fodder demand and increase the land productivity.